Pramono Anung's Digital Campaign Strategy in the Era of Cyberpolitics: Analysis of TikTok Utilization in the 2024 Jakarta Regional Elections - Rahma Nanda Azizah; Al Ziden Farel Jabriel, Alief; Pratiwi, Amalia; Marsya Luthfia, Haifa; Prakoso Aji, Muhammad (ARRUS Journal of Social Sciences and Humanities, 2025)
The phenomenon of cyber politics highlights the increasing role of social media as a contemporary political arena. The Jakarta 2024 regional election demonstrates how candidates employ digital platforms, particularly TikTok, to shape political images and attract public support. This study focuses on the digital campaign strategy of Pramono Anung, who utilized TikTok as his main instrument in building leadership image and consolidating political support. This research applies a quantitative approach using content analysis and critical discourse analysis of Tiktok campaign materials during the Jakarta 2024 election. The findings are expected to explain how Tiktok contributed to Pramono Anung’s victory within the framework of cyberpolitics, as well as enrich the literature on digital political communication strategies in Indonesia. Keywords: cyberpolitics, digital campaign, Tiktok, Pramono Anung, Jakarta 2024 election